The Diagnosis and Treatment of Local Complications of Acute Necrotizing Pancreatitis in China: A National Survey - Xiaowu Dong; Wenjian Mao; Lu Ke; Lin Gao; Jing Zhou; Bo Ye; Gang Li; Anthony Phillips; Zhihui Tong; John Windsor; Weiqin Li; Chinese Acute Pancreatitis Clinical Trials Group (CAPCTG) (Gastroenterology Research and Practice)
Background. The optimal management strategy in acute necrotizing pancreatitis (ANP) is debated, and compliance with current guidelines in China is not known. In this study, we performed a national survey on this topic in China. Methods. An online questionnaire about the diagnosis and treatment of local complications of ANP was distributed through a national collaborative network. The local and systemic complications were defined according to the Revised Atlanta Classification. Results. There were 321 survey respondents from the 394 who opened the link (response rate 81%) from 208 hospitals located in 30/34 provinces across China. There was a lack of consensus in terms of early diagnosis of infected pancreatic necrosis (IPN) as the respondents chose to depend on clinical symptoms (70/321, 22%), organ failure (82/321, 26%), imaging changes (84/321, 26%), and fine needle aspiration (51/321, 16%), respectively. A “step-up” approach has been widely adopted in patients with IPN (294/321, 92%). The decision for initial intervention (without confirmed/suspected infection) was based on clinical condition, CT imaging, or laboratory indicators for most respondents (229/321, 71%). Conclusion. While the “step-up” approach has been widely adopted, there is still significant variation in regard to the diagnosis of infection, the best timing for drainage, and the indications for early intervention.